Chitosan hydrogels embedding hyper-crosslinked polymer particles as reusable broad-spectrum adsorbents for dye removal. (1st December 2017) - Salzano de Luna, Martina; Castaldo, Rachele; Altobelli, Rosaria; Gioiella, Lucia; Filippone, Giovanni; Gentile, Gennaro; Ambrogi, Veronica
Graphical abstract: Highlights: Composite chitosan-based hydrogels for dye removal applications are prepared. Synergic effect between chitosan and hypercrosslinked polymer particles is obtained. Composite chitosan-based hydrogel works as broad-spectrum adsorbent. Adsorption properties of the composite hydrogel are higher than other biosorbents. Mechanical properties are improved and the adsorbents can be easily regenerated. Abstract: The removal of dye and toxic ionic pollutants from water is an extremely important issue that requires systematic and efficient adsorbent preparation strategies. To address this challenge, we developed composite chitosan (CS)-based hydrogels containing hyper-crosslinked polymer (HCP) particles to be used as broad-spectrum adsorbents. The goal is to efficiently combine the dye adsorption ability of chitosan and the capacity of the porous particles of trapping pollutant molecules. The HCP particles are well distributed and firmly embedded into the chitosan matrix and the composite hydrogels exhibit improved mechanical properties. Adsorption experiments reveal a synergistic effect between CS and HCP particles, and the samples are able to remove both anionic and cationic dyes (indigo carmine, rhodamine 6G and sunset yellow) from water. The maximum dye uptake is higher than that of comparable biosorbents. Moreover, the mechanical properties of the composite hydrogels are enhanced respect to pure CS, and the samples can be regenerated and reused keeping their adsorption ability unaltered over successive cycles of adsorption, desorption, and washing.